NON-PROBABILISTIC RELIABILITY ANALYSIS METHOD BASED ON INTERVAL ANALYSIS - MA DongJuan; LIU BoYing; LI LingLing (Jixie qiangdu, 2015)
when uncertainty information is not enough that it is so difficult to get the parameter probability model,the nonprobabilistic reliability analysis method could be taken into accout. This method described system parameters as interval variables first,measuring the system reliability through the ratio of security domain and the basic interval variables total area. Provided the calculation methods for probability of failure surface under different cases of combination of stress and intensity. Compared and analyzed the relationship between probability of reliability and non-probabilistic reliability when stress and intensity obey uniform distribution and normal distribution respectively. Finally,through typical numerical examples testified this analysis method.